2024
DOI: 10.1007/s44217-024-00098-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring social-emotional learning in China: a mixed-methods study with Chinese early childhood teachers

Zhengxing Zong,
Weipeng Yang,
Yixun Li

Abstract: The present study explored how Chinese early childhood teachers’ self-perceptions of their pedagogical content knowledge, beliefs, and attitudes towards Social-Emotional Learning (SEL) differ based on their backgrounds. Additionally, this research explored teachers’ understanding of their knowledge, beliefs, and attitudes towards SEL. The study involved surveying 167 early childhood teachers using the Pedagogical Content Knowledge Scale and the SEL Beliefs and Attitudes Scales, as well as conducting semi-struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Reflecting their academic-and examination-oriented education systems, East Asian societies, especially China (Zong et al, 2024), Hong Kong (Wu & Mok, 2017), and Taiwan (Wilkinson & Kao, 2019), tend to prioritize academic pursuits over SEL. Even if teachers desire to integrate SEL in their teaching, there appears to be a lack of professional learning in SEL, let alone SET strategies, for teachers in these Chinese cultural contexts.…”
Section: Cultural Variations and Educational Priorities In Selmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting their academic-and examination-oriented education systems, East Asian societies, especially China (Zong et al, 2024), Hong Kong (Wu & Mok, 2017), and Taiwan (Wilkinson & Kao, 2019), tend to prioritize academic pursuits over SEL. Even if teachers desire to integrate SEL in their teaching, there appears to be a lack of professional learning in SEL, let alone SET strategies, for teachers in these Chinese cultural contexts.…”
Section: Cultural Variations and Educational Priorities In Selmentioning
confidence: 99%
“…Even if teachers desire to integrate SEL in their teaching, there appears to be a lack of professional learning in SEL, let alone SET strategies, for teachers in these Chinese cultural contexts. For instance, in surveying 167 kindergarten teachers teaching and interviewing 10 of them in China, Zong et al (2024) found that while demonstrating a positive disposition toward SEL as critical to children's overall development, these teachers lacked pedagogical content knowledge to effectively implement SEL in their daily classroom activities. In the case of Hong Kong, early childhood education there often let propositional learning and knowledge acquisition take precedence over other aspects of children's growth, especially SEL (Wilkinson & Kao, 2019).…”
Section: Cultural Variations and Educational Priorities In Selmentioning
confidence: 99%